2021
DOI: 10.3389/fmed.2021.756337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plasma Triglyceride-Lowering Therapy on the Evolution of Organ Function in Early Hypertriglyceridemia-Induced Acute Pancreatitis Patients With Worrisome Features (PERFORM Study): Rationale and Design of a Multicenter, Prospective, Observational, Cohort Study

Abstract: Background: Acute pancreatitis (AP) is a potentially life-threatening inflammatory disease with multiple etiologies. The prevalence of hypertriglyceridemia-induced acute pancreatitis (HTG-AP) has been increasing in recent years. It is reported that early triglyceride (TG) levels were associated with the severity of the disease, and TG- lowering therapies, including medical treatment and blood purification, may impact the clinical outcomes. However, there is no consensus regarding the optimal TG-lowering therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…[57] Similarly, some other well-conducted studies also reported that higher TG level in AP patients may be linked to adverse prognosis. [58,59] The related pathophysiological mechanism has been mentioned already in our discussion. Blood puri cation, medical treatment with heparin and/or insulin can help in improve triglycerides and further promote the recovery of HTG-AP patients.…”
Section: Discussionmentioning
confidence: 58%
“…[57] Similarly, some other well-conducted studies also reported that higher TG level in AP patients may be linked to adverse prognosis. [58,59] The related pathophysiological mechanism has been mentioned already in our discussion. Blood puri cation, medical treatment with heparin and/or insulin can help in improve triglycerides and further promote the recovery of HTG-AP patients.…”
Section: Discussionmentioning
confidence: 58%
“…However, the benefits of these interventions to the overall outcome of HTG-AP are controversial. More randomized clinical trials would contribute to proposing a generalized and effective treatment modality for HTG-AP in the future [ 26 , 42 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from each participant or their next of kin. The full protocol of the PERFORM study and the analysis plan of this study were published previously . This report follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline for observational studies …”
Section: Methodsmentioning
confidence: 99%